Borylated norbornadiene derivatives: Synthesis and application in Pd-catalyzed Suzuki–Miyaura coupling reactions - Schulte, Robin; Ihmels, Heiko (Beilstein Journal of Organic Chemistry, 2022)
The photochromic norbornadiene/quadricyclane system is among the most promising candidates for molecular solar thermal (MOST) energy storage. As in this context there is still the need for new tailor-made derivatives, borylated norbornadienes were synthesized that may be used as versatile building blocks. Thus, the 4,4,5,5-tetramethyl-2-(bicyclo[2.2.1]heptadien-2-yl)-1,3,2-dioxaborolane was prepared and shown to be a suitable substrate for Pd-catalyzed Suzuki–Miyaura coupling reactions with selected haloarenes. It was demonstrated exemplarily that the novel monosubstituted 2-(1-naphthyl)norbornadiene, that is accessible through this route, is transformed to the corresponding quadricyclane upon irradiation, whereas the back reaction can be accomplished by thermal treatment.
Keywords: molecular solar thermal system; Pd-mediated catalysis; photochemistry; photoswitches; quadricyclanes